PERAN LEMBAGA PENDIDIKAN DASAR DALAM PELESTARIAN BAHASA DAERAH DAN IMPLIKASINYA TERHADAP KETAHANAN BUDAY (Studi Di Sekolah Dasar Negeri I Prambanan Dan Sekolah Dasar Islam Terpadu Salsabila Baiturrahman, Kecamatan Prambanan, Kabupaten Klaten) - Wati, Dwi Chrisna (Jurnal Ketahanan Nasional, 2014)
Elementary education institution had strategic roles in preserving local language. Those roles were (1) School as local language learning facility (2) School as student character education facility (3) School as self development facility. The purpose of this research was to measured the elementary educationâs role to supported the culture resilience. The research was conducted with questionnaire which was given by the school to the studentâs parent and also the interview to the students, teachers, and the community. The collected data were analyzed therefore this research was categorized as qualitative descriptive research. Its implication on culture resilience was the role to established studentâs interest in using Javanese language to strengthened culture resilience. Javanese language as the local culture identity and the struggling interest in local culture were to established cultural resilience.Keywords: Role, Preserving Local Language, Cultural Resilience.